Effects of Issue‐Specific Political Advertisements in the 2015 Parliamentary Elections of Switzerland. Issue 4 (10th December 2018) - Zumofen, Guillaume; Gerber, Marlène
Abstract: Our paper captures the influence of political advertisements on vote intentions in the framework of the 2015 parliamentary elections. We focus on the two winning parties, the FDP and SVP, and the promotion of their stances on immigration/asylum, relations to the EU and the economy. We make use of an extensive database on political advertisements collected in 50 important national and regional newspapers that we link to the Selects respondents. Our findings only hint at limited effects of issue‐specific advertisements with regard to the activation of latent preferences, suggesting that campaigns mattered more when they have managed to make a party's issue positions known to the electorate. The general reinforcement tendencies detected for migration ads of the SVP suggest that reinforcement effects might be particularly prone when highly contentious issues are at stake. Our results indicate that the SVP did not manage to mobilize new voters with their political advertisements.